Spatio‐temporal analysis of female breast cancer incidence in Shenzhen, 2007–2012. Issue 3 (14th May 2015) - Zhou, Hai‐Bin; Liu, Sheng‐Yuan; Lei, Lin; Chen, Zhong‐Wei; Peng, Ji; Yang, Ying‐Zhou; Liu, Xiao‐Li
Abstract: Introduction: Breast cancer is a leading tumor with a high mortality in women. This study examined the spatio‐temporal distribution of the incidence of female breast cancer in Shenzhen between 2007 and 2012. Methods: The data on breast cancer incidence were obtained from the Shenzhen Cancer Registry System. To describe the temporal trend, the average annual percentage change (AAPC) was analyzed using a joinpoint regression model. Spatial autocorrelation and a retrospective spatio‐temporal scan approach were used to detect the spatio‐temporal cluster distribution of breast cancer cases. Results: Breast cancer ranked first among different types of cancer in women in Shenzhen between 2007 and 2012 with a crude incidence of 20.0/100, 000 population. The age‐standardized rate according to the world standard population was 21.1/100, 000 in 2012, with an AAPC of 11.3%. The spatial autocorrelation analysis showed a spatial correlation characterized by the presence of a hotspot in south‐central Shenzhen, which included the eastern part of Luohu District (Donghu and Liantang Streets) and Yantian District (Shatoujiao, Haishan, and Yantian Streets). Five spatio‐temporal cluster areas were detected between 2010 and 2012, one of which was a Class 1 cluster located in southwestern Shenzhen in 2010, which included Yuehai, Nantou, Shahe, Shekou, and Nanshan Streets in Nanshan District with an incidence of 54.1/100, 000 and a relative risk of 2.41; the other four were Class 2 clusters located in Yantian, Luohu, Futian, and Longhua Districts with a relative risk ranging from 1.70 to 3.25. Conclusions: This study revealed the spatio‐temporal cluster pattern for the incidence of female breast cancer in Shenzhen, which will be useful for a better allocation of health resources in Shenzhen.